2015
DOI: 10.1111/1467-6427.12095
|View full text |Cite
|
Sign up to set email alerts
|

Bulimia nervosa in adolescents: a new therapeutic frontier

Abstract: Enhanced cognitive behaviour therapy (CBT-E) is the first-line treatment for bulimia nervosa (BN) in adulthood. There is limited evidence for therapies for children and adolescents with BN; however family-based treatment (FBT) is being increasingly used. This case study contrasts the delivery of FBT with an augmented version (CBT-E) in two adolescents presenting with BN. In both cases, the adolescents achieved remission from BN symptoms, (cessation of bingeing and compensatory behaviour) at the end of treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…For AN, three case series [70][71][72] and two case reports [73,74] indicate improved weight and psychological symptoms with added modules on perfectionism or exposure ( Table 7). For BN, one case control study exists that compared one patient treated with FBT plus CBT to another patient treated with FBT alone, finding that both patients improved in terms of binge/purge symptoms and Eating Disorder Examination (EDE) scores [75] (Table 8).…”
Section: Adjuncts To Family-based Treatment For Anorexia Nervosamentioning
confidence: 99%
“…For AN, three case series [70][71][72] and two case reports [73,74] indicate improved weight and psychological symptoms with added modules on perfectionism or exposure ( Table 7). For BN, one case control study exists that compared one patient treated with FBT plus CBT to another patient treated with FBT alone, finding that both patients improved in terms of binge/purge symptoms and Eating Disorder Examination (EDE) scores [75] (Table 8).…”
Section: Adjuncts To Family-based Treatment For Anorexia Nervosamentioning
confidence: 99%
“…Adolescents had significantly lower satisfaction with care across treatments compared to parents, though a non-significant trend favored adolescent satisfaction with CBT outpatient care compared to general community care Fair a Hilbert et al (2020) [ 47 ] RCT BED 15.3 [12–20] CBT (32) vs WLC (36) 32 20 sessions over 4 mo 6 mo 12 mo 24 mo Compared to WLC group, CBT group had significantly higher rates of abstinence from binge eating (51% vs. 33%) and remission from BED (57% vs. 33%) and significantly less ED psychopathology at EOT (EDE). CBT group maintained its advantage relative to WLC in in ED behaviors and psychopathology at all FU timepoints Good a Hurst et al (2017) [ 83 ] Case study BN 15 [15–15] FBT-BN (1) versus FBT-BN + CBT (1) 0 Not reported None Participants in both treatments achieved full remission at EOT (EDE global score within 1 SD of community norms). Participant 1 reduced binge and purge episodes from an average of 12 per week at BL, to 100% abstinence at EOT.…”
Section: Methodsmentioning
confidence: 99%